Electrochemical Sensor Based on a MXene Nanosheet-Gold Nanourchin Hybrid as a Superoxide Dismutase Mimic for Real-Time Detection of Superoxide Anions Released from Living Cells - Nandi I.; Kumari R.; Kachhawaha K.; Singh S.K.; Chandra P. (My University, 2025)
The superoxide anion radical (O2•-) is produced as a byproduct of regular cellular respiration and plays crucial roles in numerous cellular functions, including homeostasis, cell proliferation, migration, and apoptosis. However, when its regulation is disrupted, it is linked to various illnesses, including cancer, autoimmune diseases, cardiovascular diseases, neurodegenerative diseases, etc. Hence, developing precise detection methods for O2•- measurement has recently drawn much scientific attention. Herein, we report the fabrication of a nanoscale hybrid comprising MXene nanosheets-gold nanourchin (MXene/AuNU) at the electrode surface and its subsequent application for the in vitro detection of O2•- radicals. The nanoscale hybrid served as a mediator- and receptor-less sensing probe with superoxide dismutase (SOD) enzyme-mimicking catalytic properties. Several electrochemical and physical approaches were used to characterize it thoroughly. The chronoamperometric responses of the developed electrode were proportional to the concentration of O2•- radicals within the wide linear dynamic range (LDR) of 10-10 to 5 × 10-5 M. The limit of detection (LOD) was found to be 56.74 ± 0.56 pM, which was significantly lower in comparison to those of recent reports. The novel nanozyme platform could also efficiently detect the catalytic product of superoxide, hydrogen peroxide (H2O2), with a high peak resolution. The proposed probe successfully and sensitively assessed O2•- radicals released from live cells, revealing its immense practical applicability for real-time detection. © 2024 American Chemical Society.